VizieR Online Data Catalog: XMM-Newton point-source catalogue of the SMC (Sturm+, 2013) - Sturm, R.; Haberl, F.; Pietsch, W.; Ballet, J.; Hatzidimitriou, D.; Buckley, D. A. H.; Coe, M.; Ehle, M.; Filipovic, M. D.; La Palombara, N.; Tiengo, A. (2013)
The XMM-Newton survey of the Small Magellanic Cloud (SMC) yields a complete coverage of the bar and eastern wing in the 0.2-12.0keV band. This catalogue comprises 3053 unique X-ray point sources and sources with moderate extent that have been reduced from 5236 individual detections found in observations between April 2000 and April 2010. Sources have a median position uncertainty of 1.3" (1σ) and limiting fluxes down to ~1*10-14erg/s/cm2 in the 0.2-4.5keV band, corresponding to 5*1033erg/s for sources in the SMC. Sources have been classified using hardness ratios, X-ray variability, and their multi-wavelength properties. In addition to the main-field (5.58deg2) available outer fields have been included in the catalogue, yielding a total field area of 6.32deg2. X-ray sources with high extent (>40", e.g. supernova remnants and galaxy cluster) have been presented by Haberl et al. (2012, Cat. J/A+A/545/A128) (2 data files).
Keywords: Magellanic Clouds; Surveys; X-ray sources